Pengaruh Kualitas Pelayanan terhadap Kepuasan Publik di Kantor Radio Republik Indonesia, Malang - Harianti, Nunuk; Alhabsy, Taher; Soekarto, Soekarto (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purposes of this research were describe the public service quality and public satisfaction at RRI Malang Office; identify and explain the influence of the effect of reliability, responsiveness, assurance, empathy, and tangibles simultaneously towards public satisfaction of the public; as well as identify and explain the influence reliability, responsiveness, assurance, empathy, and tangibles in most of public satisfaction. Method of this research used explanatory research. Results of this study concluded that description of quality licensing services to public satisfaction can be shown and described through five (5) variables, namely: tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5). This research showed that people who receive services from the Office of RRI Malang as respondents got positive respond towards these variables. By knowing the value of the influence of each variables, then it can be concluded that the dominant variable of public satisfaction in this research were reliability variable.